Clinical outcome of the late preterm infants (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
The aim of this retrospective study was to evaluate the short-term clinical outcome of late preterm babies (34-36 week) in a tertiary level hospital from January 2013 to December 2014. A total of 3,749 babies were delivered during this period of which 513 were late preterm. Among the late preterm babies, 481 babies were delivered by cesarean section. Admission to the neonatal intensive care unit after birth was needed in case of 66 babies. Higher incidences of complication like jaundice (14.4%), sepsis (6.2%), respiratory distress syndrome (2.9%), transient tachypnea (2.3%) and others were found in comparison to control term babies. Ventilation was required in 11 cases. Late preterm mortality was 1.4%. In conclusion, late prematurity is associated with significant neonatal morbidity and mortality.